2004
DOI: 10.1081/ncn-200027714
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fluoropyrimidines on the Growth ofUreaplasma urealyticum

Abstract: In the present study, we investigated the effect of fluoropyrimidines on the growth of Ureaplasma urealyticum. Addition of fluoropyrimidines strongly inhibited bacterial growth. Growth inhibition by these analogues could be reversed by addition of either thymidine or deoxyuridine, suggesting inhibition of thymidylate biosynthesis as the mechanism in operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…Halogenated pyrimidine analogs such as 5FdU inhibited Mpn and Ureaplasma growth, as reported in our earlier studies [30,35]. Others have shown that TFT and 5FdU inhibited Cryptosporidium growth [47], and gemcitabine inhibited Staphylococcus aureus growth in vitro and in animal models [48].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Halogenated pyrimidine analogs such as 5FdU inhibited Mpn and Ureaplasma growth, as reported in our earlier studies [30,35]. Others have shown that TFT and 5FdU inhibited Cryptosporidium growth [47], and gemcitabine inhibited Staphylococcus aureus growth in vitro and in animal models [48].…”
Section: Discussionsupporting
confidence: 78%
“…Some nucleoside analogs have been reported to inhibit Mycoplasma growth [30,35]. Recently a nucleoside and nucleobase analog library consisting of FDA-approved prodrugs used in anticancer and antiviral therapy was used to screen human enzymes in nucleotide metabolism, and new interactions were found [36], which promoted the use of these analogs in screening for inhibitory effects on Mpn growth.…”
Section: Resultsmentioning
confidence: 99%
“…Various fluorinated pyrimidines could inhibit the growth of the human pathogen Ureaplasma urealyticum (Carnrot et al, 2003). Floxuridine had a strong effect in vitro, inhibiting the growth of U. urealyticum for up to 72 h. This finding was supported by a later study (Wehelie et al, 2004). Subsequently, various Gram-positive and Gram-negative bacteria were found to be susceptible to floxuridine (Sandrini et al, 2007a,b;Zander et al, 2010a).…”
Section: Fluorinated Pyrimidinesmentioning
confidence: 89%
“…Troemel et al added 5-fluorodeoxyuridine (FUDR) to NGM plates seeded with OP50, to prevent C. elegans progeny. However, FUDR acts to inhibit DNA synthesis, and also inhibits bacterial proliferation [76]. That abrogating two host anti-bacterial mechanisms (e.g.…”
Section: Discussionmentioning
confidence: 99%